Evaluation of regular and decaffeinated (un)roasted coffee beans using HPLC and multivariate statistical methods - Klikarová, Jitka; Řeháková, Barbora; Česlová, Lenka (My University, 2022)
This work deals with the rapid simultaneous determination of caffeine and the three most abundant chlorogenic acid isomers (3-, 4-, and 5-O-caffeoylquinic acids) present in 64 samples of regular (un)roasted and decaffeinated (un)roasted coffee beans using reversed-phase high-performance liquid chromatography with spectrophotometric detection. In the developed method, the target analytes were separated in just 6 min with a resolution higher than 1.2. Afterwards, factor analysis and principal component analysis were employed to reveal the relationships between the samples and the content of monitored compounds. The samples were successfully divided into three discrete groups (decaffeinated, roasted, and unprocessed) by these methods. Finally, the impact of sample roasting and decaffeination on the content of chlorogenic acid isomers was investigated. The decrease in 5-O-caffeoylquinic acid concentration during the decaffeination process was found not as significant as during the roasting process. Regarding caffeine isolation, dichloromethane was the best extraction solvent because it did not cause significant losses of chlorogenic acid isomers or changes in the coffee beans colour and its extraction efficiency reached 85%.
Hodnocení běžných a bezkofeinových (ne)pražených kávových zrn pomocí HPLC a vícerozměrných statistických metod
Keywords: chlorogenic acid isomers; caffeine; coffee beans; decaffeination; HPLC; multivariate data treatment.; Izomery chlorogenové kyseliny; kofein; kávová zrna; dekofeinace; HPLC; vícerozměrné statistické metody